(untitled) (Open Herald: Periodical of Methodical Research, 2024)
A detailed study of the risk factors associated with the development of MI in men allows us to identify their age characteristics. The creation of a calculator for predicting the development of MI, taking into account the age characteristics of risk factors in men, is relevant for the possibility of identifying risk groups during occupational examinations, medical examinations, primary therapeutic examination for further application of a differentiated and individual approach to the prevention of MI.